Mucopolysaccharidase of Treponema pallidum - Fitzgerald, T. J. (1979)
Treponema pallidum (Nichols strain) exhibited mucopolysaccharidase activity. Acidic mucopolysaccharides were broken down more rapidly by viable treponemes than by heat-inactivated treponemes or membrane filtrates of treponemal suspensions. Ouchterlony immunodiffusion demonstrated the occurrence of antibodies to the hyaluronidase-like enzyme within syphilitic sera. After intratesticular inoculation of 2 × 10(7) to 6 × 10(7) treponemes, these anti-mucopolysaccharidase antibodies were detected between 9 and 35 days postinoculation. In addition, acidic mucopolysaccharides were present in the serum of infected animals 9 and 16 days postinoculation. Immune serum that contained antibodies to the mucopolysaccharidase restricted treponemal breakdown of acidic mucopolysaccharides. It has been previously demonstrated that immune rabbit serum contains a factor that blocks attachment of T. pallidum (Nichols strain) to cultured mammalian cells. This factor was effectively absorbed by prior incubation with bovine hyaluronidase. It is postulated that T. pallidum attaches to acidic mucopolysaccharides on the surface of cultured cells through the mucopolysaccharidase enzyme at the surface of the organisms. These findings are discussed in terms of the histopathogenesis of T. pallidum with applications to the healing immune response.